What Works in Coping With HIV? A Meta-Analysis With Implications for Coping With Serious Illness. [article]. - Moscowitz, Judith Tedlie
Knowledge of effective of coping with HIV is critical to help individuals with HIV maintain the best possible psychological and physical weel-being. The purpose of the present article is to determine, through meta-analysis, the strength of evidence regarding 2 questions: (a) which types of coping are related to psychological and physical well-being among people with HIV? and (b) Do contextual (pre-post introduction of highly active antiretroviral therapies [HAART]; time since diagnosis), measurement (HIV-related event vs generic prompts for coping measurement), or individual (gender) variables affects the extent to which coping is related tomphysical and psychological well-being? The authors' analysis demonstrates tha Direct Action and Positive Reappraisal were consistently associated with better outcomes in people coping with HIV across affective, health behavior, and physical health categories. In contrast, disengagement forms of coping, such as Behavioral Disengagement and Use of Alcohol or Drugs to Cope, were consistently associated with poorer outcomes. The findings also indicate that in some cases, coping effectiveness was dependent on contextual factors, including time since diagnosis and the advent of HAART. -- (from the author)
Keywords: Coping; Positive affect; Negative affect; Health behavior; Physical health